Modern Russian Poetry in Olympiad Assignments in Literature (Филологический класс, 2021)
The article discusses approaches to a holistic analysis of poetic texts of the 21st century at Literature Olympiads. The main aim of this academic activity of senior schoolchildren is to teach them to demonstrate their own understanding of a poem through considering it as an integral unity of elements and analyzing the most essential features of its artistic structure. The author answers the following questions: what knowledge, skills, competences are tested by assignments on contemporary poetry? What poetics features of modern literature require special attention and how to teach senior schoolchildren to carry out analysis correctly? How can “Olympiad” poetry be of interest to a modern secondary schooler? On the material of the poems by Polina Barskova, Alexei Tsvetkov and Vladimir Gandelsman the article shows possible ways of text analysis that have formed in practical work – primarily in the Sirius educational center (Sochi). The author uses P. Barskova’s poem “Happiness” (2001), included in the tasks of the final stage of the 2019 Literature Olympiad, to show the methods of work with subtext / intertext and subject structure. The relationship between the object-based and symbolic plans, of the empirically “true-to-life” plot and the biblical subtext are in the focus of attention during the analysis of A. Tsvetkov’s poem “The experience of the end of the world” (2019). V. Gandelsman’s poem “In the morning, right after dawn, I am at the foot…” (2018) was offered to students at a trial competition in “Sirius”. The article contains excerpts from the works of secondary school students, showing how they interpreted the poem.